The Variations of the English Noun Postmodifiers in The Undergraduate Students’ Compositions - Ariwibowo, Seto; Tedjasuksmana, Hendra (Beyond Words, 2018)
This study investigated the acquisition of English noun post-modifiers in the compositions written by Writing III students of the English Department of Widya Mandala Catholic University Surabaya. It sought to discover the variations of English noun postmodification constructions, their complexity level, their accuracy, and their efficiency found in the end-of-term compositions of the students of Widya Mandala Catholic University Surabaya. The types of noun postmodifications, their complexity level, their accuracy, and efficiency of use may reflect the students’ level acquisition of the structures of the English noun post-modifications. The result showed eight of the nine types of postmodifiers were present, while one type was absent. The preposition phrase was the most dominant type postmodifier with 65.235% of occurrences. The embedding of the postmodified nouns was dominated by the zero embedding, while the rate of the single postmodification was also significantly high. Such dominances of preposition phrase, the zero embedding, and single postmodification, and the presence of such cases of lengthy and ambiguous structures noun postmodification indicate the students’ level of complexity of the structure of English noun postmodification, accuracy, and efficiency of the English noun postmodifications.